Factors influencing the probability of a diagnosis of autism spectrum disorder in girls versus boys. (August 2017) - Duvekot, Jorieke; van der Ende, Jan; Verhulst, Frank C; Slappendel, Geerte; van Daalen, Emma; Maras, Athanasios; Greaves-Lord, Kirstin
In order to shed more light on why referred girls are less likely to be diagnosed with autism spectrum disorder than boys, this study examined whether behavioral characteristics influence the probability of an autism spectrum disorder diagnosis differently in girls versus boys derived from a multicenter sample of consecutively referred children aged 2.5–10 years. Based on information from the short version of the Developmental, Dimensional and Diagnostic Interview and the Autism Diagnostic Observation Schedule, 130 children (106 boys and 24 girls) received a diagnosis of autism spectrum disorder according to Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev.) criteria and 101 children (61 boys and 40 girls) did not. Higher overall levels of parent-reported repetitive and restricted behavior symptoms were less predictive of an autism spectrum disorder diagnosis in girls than in boys (odds ratio interaction = 0.41, 95% confidence interval = 0.18–0.92, p  = 0.03). In contrast, higher overall levels of parent-reported emotional and behavioral problems increased the probability of an autism spectrum disorder diagnosis more in girls than in boys (odds ratio interaction = 2.44, 95% confidence interval = 1.13–5.29, p  = 0.02). No differences were found between girls and boys in the prediction of an autism spectrum disorder diagnosis by overall autistic impairment, sensory symptoms, and cognitive functioning. These findings provide insight into possible explanations for the assumed underidentification of autism spectrum disorder in girls in the clinic.